Internet Usage and Its Impact on The Physical and Mental Health of The Elderly in China - Meixia, Qu; Ali, Isahaque; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2025)
This study examines the relationship between internet usage and the mental and physical health of elderly individuals in China using data from the 2021 China General Social Survey (CGSS). Employing an ordered logistic regression model, the research explores how internet usage influences the health of the elderly. The findings reveal a significant positive correlation between internet use and health outcomes of the elderly population. Elderly internet users demonstrate 10.8% and 6.7% higher physiological and mental health compared to non-users. However, using the internet as the primary information source significantly impairs physical health, while leisure-time internet use also negatively affects health. Moreover, the health impacts vary by demographic characteristics – married, male, more educated, and Communist Party member elderly benefit more. Overall, internet use can elevate the health levels of older adults but negative effects also exist. It is necessary to balance usage time and implement tailored interventions to promote the overall well-being of the elderly. Key recommendations include: advocating diversified internet use; promoting digital literacy; strengthening offline social connections. This research provides important insights into understanding the impacts of internet use on the health of the aging population in China, informing policies to improve their well-being in the digital age.